2014
DOI: 10.3389/fpubh.2014.00266
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of Pediatric Cases Handled by the MSF Tele-Expertise System

Abstract: We conducted a retrospective analysis of all pediatric cases referred by Médecins Sans Frontières (MSF) field doctors via the MSF telemedicine system during a 4-year period from April 2010. A total of 467 pediatric cases were submitted, representing approximately 40% of all telemedicine cases. The median age of the patients was 4 years. The median response time (i.e., the interval between the case being submitted and the first response from a specialist) was 13 h (interquartile range 4–32 h). We selected a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, the reliable application of this technology in resource-limited settings can be challenging. The MSF system demonstrated a median response time of 13 h making its utility in critical, time-sensitive cases, somewhat limited ( 98 ).…”
Section: Critical Care Infrastructure and Capacity Building In Resourmentioning
confidence: 99%
“…However, the reliable application of this technology in resource-limited settings can be challenging. The MSF system demonstrated a median response time of 13 h making its utility in critical, time-sensitive cases, somewhat limited ( 98 ).…”
Section: Critical Care Infrastructure and Capacity Building In Resourmentioning
confidence: 99%
“…Many published studies showed the experience of asynchronous telemedicine in different countries with low resources (4)(5)(6)(7)(8). Perhaps it is a type of telemedicine of easier applicability in low-income countries, due to the difficulty in accessing the internet and other cost-effectiveness studies have showed the benefits of the national implementation of telemedicine programs in countries such as Botswana or Cape Verde (4)(5)(6). In Angola, in 2007, the PEDITEL project (Pediatric Telemedicine) was implemented, which was a synchronous telemedicine project.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a retrospective analysis and user survey, Bonnardot et al ( 14 ) provide a general overview of the system and the user perceptions of it. The three main specialties used in the network are radiology, pediatrics, and dermatology, which were reviewed by Halton et al ( 15 ), Delaigue et al ( 16 ), and Martinez Garcia et al ( 17 ), respectively.…”
mentioning
confidence: 99%